"Spiritual Enlightenment”: Understanding and Preventing Corruption through Al-Quran Principles - Prayogo, Agung; Siregar, Muklis; Harahap, Mardian Idris (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2024)
The politics of corruption in Indonesia has become an electoral culture for personal and group interests that makes people miserable. Indonesia itself is ranked 110th out of 180 countries in the world for corruption cases, so serious efforts are needed to prevent corrupt practices. The article uses qualitative research using the Maudu'i method by connecting verses from the Koran related to the topic of corruption. Primary data is the Koran, while secondary data comes from journal articles, web data and news related to corruption. This article explains the definition of corruption in the Koran and the urgency of corruption which clearly endangers the state, especially the role of the state in the welfare of the people. The verses of the Koran clearly provide instructions and prohibitions on corrupt practices which are prohibited in Islam. Islam itself explains that corrupt practices have existed since the time of the Prophet as described in the verses of the Koran. This article offers efforts to prevent corruption, including protecting the people by providing a sense of security, enforcing the law fairly, character revolution, increasing human resources through religious education.